Analyzing the User Behavior toward Electronic Commerce Stimuli - Lorenzo-Romero, Carlota; Alarcón-del-Amo, María-del-Carmen; Gómez-Borja, Miguel-Ángel (Frontiers in Behavioral Neuroscience, 2016)
Based on the Stimulus-Organism-Response paradigm this research analyzes the main differences between the effects of two types of web technologies: Verbal web technology (i.e. navigational structure as utilitarian stimulus) versus nonverbal web technology (music and presentation of products as hedonic stimuli). Specific webmosphere stimuli have not been examined yet as separate variables and their impact on internal and behavioral responses seems unknown. Therefore, the objective of this research consists in analyzing the impact of these web technologies –which constitute the web atmosphere or webmosphere of a website– on shopping human bebaviour (i.e. users’ internal states -affective, cognitive, and satisfaction- and behavioral responses - approach responses, and real shopping outcomes-) within the retail online store created by computer, taking into account some mediator variables (i.e. involvement, atmospheric responsiveness, and perceived risk). A 2(“free” versus “hierarchical” navigational structure) x2(“on” versus “off” music) x2(“moving” versus “static” images) between-subjects computer experimental design is used to test empirically this research. In addition, an integrated methodology was developed allowing the simulation, tracking and recording of virtual user behavior within an online shopping environment. As main conclusion, this study suggests that the positive responses of online consumers might increase when they are allowed to freely navigate the online stores and their experience is enriched by animate gifts and music background. The effect caused by mediator variables modifies relatively the final shopping human behavior.